(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Introduction: Asthma care requires regular follow-up to adjust effective control in line to reduce asthmatic morbidity and impact society either economically or even morbidity. Nearby thousands require emergencies due to their technical misused inhalator. Aim of Study: To investigate the effect of Symbicort technical misuse on asthmatic attacks` frequency, financial cost, and emergency admission among the Iraqi population with asthma. Material and Methods: 133 participants were recruited from multiple outpatient clinics of major central hospitals in Nasiriya, Thiqar, Iraq, of both genders and were randomly assigned into two equal groups after being assigned a consent form. All participants` demographic and semi-structural data regarding the asthmatic attack, financial, cost, and technical handling were collected, tabulated then statistically analyzed. Results: Strong statistical significant positive correlation was revealed between asthmatic attacks, and emergency readmission outcomes with technical misuse 1.23(95% CI 0.76; 1.84) and 1.36(95% CI 0.65; 2.68), respectively; plus good prediction was recorded with financial costing and cassation of Symbicort 1.35(95% CI; 0.74; 1.25), 0.83(95% CI; 0.67; 0.58), respectively. Conclusion: Current clinical study shows an obvious correlation between Symbicort’s technical misuse and frequencies of asthmatic attacks, financial costs, and emergency readmissions. In addition to significant prediction of low education and limited awareness regarding Symbicort best technical handling among elder populations. Depending on our findings, it was recommended to take into consideration enforcing best technical handling at clinical regular sessions throughout asthmatic patient’s follow-up algorism in Iraq.